PERANAN PEMERINTAH DALAM PEMBERDAYAAN USAHATANI HOLTIKULTURA DI KABUPATEN BIAK NUMFOR - David J. J. D. Sabarofek; Lyndon R. J. Pangemanan; Mex L. Sondakh (Sam Ratulangi University, 2017)
The purpose of this study is to determine: (1) how the role of the Department of Agriculture in Empowering Horticulture Farmers in Biak Numfor District, (2) constraints faced by farmers in horticulture farming in Dofyo Wafor Village, North Biak District, Biak Numfor District, Papua Province. This research was conducted for 3 months starting from March until May 2017. This research uses qualitative research approach. Primary data were collected by interviews and field observations. Respondents were selected by purposive sampling method as many as 30 respondents selected from 3 farmer groups in the village of Dofyo Wafor. Secondary data collection is obtained from the literature derived from related agencies such as: Animal Husbandry and Food Crop Farming Biak Numfor District. Central Bureau of Statistics of Biak Numfor Regency. Technical Service Unit of Agricultural Extension Institute of Biak Utara District and Dofyo Wafor Village Office. Data analysis used is qualitative analysis. The research found that (1) Government in empowering horticulture farm in Biak Numfor Regency. Particularly in Dofyo Wafor Village, through the Livestock and Food Crops Office of Biak Numfor District has empowered farmers, empowerment carried out in the form of counseling, seed breeder supervisors, providing superior seed support, irrigation irrigation facilities, technological advancement, assistance in land management, and assistance in farmer institutions; (2) The existing obstacles are pest and disease attack on agricultural crops, limited knowledge, skills and capital of farmers, and also the bargaining position of agricultural products that are still low.